Perceiving gloss through transparency - Sabrina Hansmann-Roth; Pascal Mamassian (i-Perception)
The image intensity depends on the illumination, the reflectance properties of objects but also on the reflectance and absorption properties of any intervening media. In this study we present observers with glossy objects behind partially transmissive materials. The transparent layer causes an achromatic color shift and compression in luminance contrast, which can affect the perception of the specular reflections of the object behind the layer. In two distinct experiments, we examine how an achromatic color shift and the compression of luminance contrast affect perceived gloss. Thanks to the maximum likelihood conjoint measurement paradigm, we estimate the contamination of different transparent layers on perceived gloss. In the follow-up experiment, observers were asked to match the albedo and the gloss of surfaces seen in plain view to surfaces seen behind a transparent layer. Our results indicate a high degree of gloss constancy with some small but significant contribution of the transparent layer when estimating gloss, especially in the case of light-colored transparent layers. Overall, gloss is significantly overestimated.